Whole transcriptome data analysis of mouse embryonic hematopoietic stem and progenitor cells that lack Geminin expression - Patmanidi, A; Kanellakis, N; Karamitros, D; Papadimitriou, C; Lygerou, Z; Taraviras, S (Elsevier, 2016)
We performed cDNA microarrays (Affymetrix Mouse Gene 1.0 ST Chip) to analyze the transcriptome of hematopoietic stem and progenitor cells (HSPCs) from E15.5dpc wild type and Geminin (Gmnn) knockout embryos. Lineage negative cells from embryonic livers were isolated using fluorescence activated cell sorting. RNA samples were used to examine the transcriptional programs regulated by Geminin during embryonic hematopoiesis. The data sets were analyzed using the GeneSpring v12.5 platform (Agilent). The list of differentially expressed genes was filtered in meta-analyses to investigate the molecular basis of the phenotype observed in the knockout embryos, which exhibited defective hematopoiesis and death. The data from this study are related to the research article “Geminin deletion increases the number of fetal hematopoietic stem cells by affecting the expression of key transcription factors” (Karamitros et al., 2015) [1]. The microarray dataset has been deposited at the Gene Expression Omnibus (GEO) under accession GEO: GSE53056.